Restitution in the context of institutional lock-in - Załęczna Magdalena (Journal for Perspectives of Economic Political and Social Integration, 2014)
This article presents the problem of lack of restitution in Poland in the political, social and economic context. The author presents the theory of institutional lock-in, referring to the hitherto course of the political, social and economic transformation processes in Poland. She is focusing on the research problem in form of an institutional lock-in on the route to general restitution process. The author examines the path shaping and path dependence to understand the current negative attitude toward restitution presented by the government and society. The author also indicates the costs caused by lack of restitution. Through analysis of past attempts of restitution regulations the author indicates the most important flashpoints. A hypothesis constructed by the author focuses on the negative effects of institutional lock-in, lack of restitution increases transaction costs influencing the Polish economy. The study is based on the legal documents and the results of public opinion polls.